Math, asked by sadhna1432, 1 year ago

Factorise
11x^2 +19x -6


devansh898: why he is not given answer
Swarup1998: she is typing on website
devansh898: ok

Answers

Answered by MarkAsBrainliest
26
\textbf{Answer :}

Now, 11x² + 19x - 6

= 11x² + (22 - 3)x - 6

= 11x² + 22x - 3x - 6

= 11x (x + 2) - 3 (x + 2)

= (x + 2) (11x - 3),

which is the required factorization.

#\textbf{MarkAsBrainliest}
Answered by dikshaverma4you
58
Hey, I have attached the solution to your question. Kindly have a look over it. Hope it helps you. :)
Attachments:
Similar questions